PROFIT EFFICIENCY AMONG SMALL HOLDER IRRIGATED TOMATO FARMERS IN KEBBI STATE, NIGERIA. - Gona, A.; Maikasuwa, M. A.; Tomo, I. K. (IJRDO - Journal of Business Management, 2020)
Profit efficiency refers to the extent at which a firm makes not only profit but its ability to maximize profit. The study examined the Profit efficiency and its determinants among Tomato farmers in Kebbi state, Nigeria. Data were collected from a sample of 160 farmers using the multistage sampling technique. A translog stochastic frontier profit function model was employed for the analysis in which profit efficiency effects are specified to be a function of socioeconomic variables estimated using the maximum likelihood method. The results of the analysis revealed that planting material, labour, fertilizer, herbicides and manure are the dominant variables that influenced profit efficiency in Tomato production with coefficient values of (11.735, 2.143, 10.629, 80.213 and -7.065), respectively. Analysed results revealed a wide variation in the estimated profit efficiencies, ranging between 0.03 and 0.67 with a mean of 0.56 suggesting that the best profit maximizing farmer operated barely above average frontier. The result also showed that age, amount of credit accessed and membership of association positively influenced profit efficiency of Tomato farmers while farming experience, farm size planting technology and seed variety influenced profit efficiency negatively. In order to increase profit efficiency in Tomato production the farmers need to increase farm size, use improved planting technology and improved seed variety.